Potential role of Amyloid-β on the association between Orexin-A and blood-brain barrier leakage of globus pallidus in Alzheimer’s disease and dementia with lewy bodies - Jinghuan Gan; Ziming Xu; Chen Wen; Hao Wu; Zhichao Chen; Zhihong Shi; Hao Lu; Yajie Wang; Shuai Liu; Yong Ji (Alzheimer’s Research & Therapy)
Abstract Background Emerging evidence indicates that globus pallidus (GP) function can be modulated by orexin-A in movement disorders, while its role in Alzheimer’s disease (AD) and dementia with Lewy bodies (DLB) remains unclear. We have ever found the increased blood-brain barrier (BBB) permeability in GP and plasma orexin-A level were respectively correlated with plasma amyloid-β (Aβ) levels in AD and DLB. However, the interplay among these factors and their underlying mechanisms is poorly understood. Methods In this study, we measured plasma orexin-A, Aβ1–40, and Aβ1–42 levels, along with BBB permeability in GP via dynamic contrast-enhanced MRI, in 20 healthy controls (HC), 25 patients with AD, and 16 patients with DLB from December 2020 to April 2022. Demographic, clinical, and neuropsychological data were collected. The mediation analysis models were used to calculate the mediating effect of Aβ on the associations between orexin-A and BBB permeability in GP (reflected by K trans or Vp values). Results Patients with AD had significantly higher plasma orexin-A than DLB (p = 0.047) and HC (p < 0.001), while DLB showed elevated Aβ1–40 and Aβ1–42 versus AD and HC (all p < 0.05). HC had higher Vp values of right GP than AD (p = 0.037). Patients with AD displayed higher K trans for left GP and average left-right K trans than both HC and DLB (all p < 0.05). K trans and Vp values for GP correlated with MoCA, CDR, HAMD, and NPI scores in patients with AD and DLB, and with plasma orexin-A, Aβ1–40, and Aβ1–42 in HC. After adjusting for confounders, Aβ1–40 (Beta = -0.864, p = 0.021) and Aβ1–42 (Beta = -0.875, p = 0.039) partially mediated the link between orexin-A and K trans for left GP in HC. Aβ1–40 (Beta = -1.845, p = 0.042) partially mediated the link between orexin-A and K trans for right GP in DLB. No significant mediation was found in AD or across all participants. Conclusion This study elucidates the clinical role of BBB permeability in GP in AD and DLB, highlights the partial mediating effect of Aβ on the association between orexin-A and BBB leakage. These findings provide mechanistic insights into BBB dysfunction during aging and neurodegeneration.